2017
DOI: 10.1016/j.ultras.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic compaction of granular geological materials

Abstract: It has been shown that the compaction of granular materials for applications such as pharmaceutical tableting and plastic moulding can be enhanced by ultrasonic vibration of the compaction die. Ultrasonic vibrations can reduce the compaction pressure and increase particle fusion, leading to higher strength products. In this paper, the potential benefits of ultrasonics in the compaction of geological granular materials in downhole applications are explored, to gain insight into the effects of ultrasonic vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The transition is more complex though, because in mayonnaise (a Bingham plastic) this occurs at an absolute yield stress, but in granular media the breakdown (unjamming) is friction based [7], and influenced by pressure and particle shape [8]. It can also, apparently, be triggered by ultrasonic vibration [9].…”
Section: Discussionmentioning
confidence: 99%
“…The transition is more complex though, because in mayonnaise (a Bingham plastic) this occurs at an absolute yield stress, but in granular media the breakdown (unjamming) is friction based [7], and influenced by pressure and particle shape [8]. It can also, apparently, be triggered by ultrasonic vibration [9].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been reported that the powder compaction is improved by decreasing the friction of powder caused by ultrasonic vibration [1][2][3] . Generally, the powder compaction is performed with ultrasonic vibration as well as high static pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The powder compacting technique using ultrasound has been used in various industrial fields, such as, pharmaceutical, metal metallurgy, and environmental radioactive sample preparation. [1][2][3] Recently, it is known that the compaction assisted with ultrasound in the manufacturing process of tablets has brought into to increase the relative density of tablets by decreasing the porosity in the tablets and it is utilized to increase the drug efficiency per unit volume or the dissolution time of the drug. [4][5][6] Ultrasonic vibration in the powder compacting process is known to reduce the effective friction coefficient of powder.…”
mentioning
confidence: 99%